2020
DOI: 10.1136/ijgc-2020-001771
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor-2 (HER2) is a potential therapeutic target in extramammary Paget’s disease of the vulva

Abstract: BackgroundInvasive vulvar Paget’s disease with over-expression of the human epidermal growth factor receptor 2 (HER2) protein is potentially suitable for targeted therapy, especially in a metastatic setting where no effective treatments are available.MethodsFour consecutive patients with HER2 positive advanced vulvar Paget’s disease, treated with weekly trastuzumab (loading dose 4 mg/kg, then 2 mg/kg) and paclitaxel (80 mg/m2) followed by 3-weekly trastuzumab maintenance (6 mg/kg), are reported.ResultsMedian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Although anti-HER-2 therapy has been tried in very few patients, it seems to reduce tumor size, and it is well tolerated by the patients. Very recently, trastuzumab-based treatments, mostly a paclitaxel–trastuzumab combination, have been described as leading to a complete or partial response in patients with invasive vulvar PD, thus strongly indicating the possibility that HER-2 inhibitors are suitable for adjuvant therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although anti-HER-2 therapy has been tried in very few patients, it seems to reduce tumor size, and it is well tolerated by the patients. Very recently, trastuzumab-based treatments, mostly a paclitaxel–trastuzumab combination, have been described as leading to a complete or partial response in patients with invasive vulvar PD, thus strongly indicating the possibility that HER-2 inhibitors are suitable for adjuvant therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…An objective response was observed in all the patients, with a median duration of response of 10 months. Treatment was extremely well tolerated [71].…”
Section: Targeted Agentsmentioning
confidence: 98%
“…As for molecular expression in EMPD lesions, multiple studies have demonstrated HER2 overexpression in EMPD lesions, which was associated with amplified ERBB2 [55,56]. These HER2-positive EMPD cases conferred a more aggressive biology [57]. In addition, Tanaka et al demonstrated that around 90% of patients with EMPD showed no difference in HER2 overexpression and ERBB2 gene amplification between primary lesions and lymph node (LN) metastasis, indicating that targeting therapies for HER2 may be effective for the treatment of both primary and metastatic lesions [58].…”
Section: Pathogenesismentioning
confidence: 99%
“…As described above, HER2 overexpression is frequently found in EMPD lesions, and HER2 may play crucial roles in the development and progression of EMPD in cases of HER2-positive tumors. Indeed, multiple cases of HER2-positive advanced EMPD have been reported that have shown the antitumor effects of anti-HER2 antibody, trastuzumab, monotherapy, or trastuzumab combined with other chemotherapies, such as paclitaxel or carboplatin [57,[143][144][145][146][147][148]. Most of these cases showed PFS of longer than 12 months, suggesting that anti-HER2 antibody is a promising therapy for advanced EMPD.…”
Section: Anti-her2 Antibody Therapymentioning
confidence: 99%